Skill Test of Workers from Informal Sectors for their Recognition and Employability: A Thematic Study - Poudel, Ajay (Journal of Technical and Vocational Education and Training, 2024)
This thematic review explores the significance of skill tests and recognition for the informal sector workers by employing a systematic approach to unveil recurring themes: validation of skills, employability enhancement, recognition and accreditation. The validation of skills emerged as a cornerstone, boosting confidence and motivation. Skill tests and recognition play a pivotal role in enhancing job prospects for informal sectors' workers, equipping them with a competitive edge. Moreover, recognition and accreditation are crucial for establishing the credibility of informal learning achievements. Implications for informal sectors' workers include increased confidence, employability and credibility. Policymakers are urged to integrate systematic recognition processes to foster a culture that values and empowers informal sectors' workers.